Minimising construction disputes - Wahi, Noraziah (2008)
Construction industry plays an important role in developing Malaysia and it is a major contributor towards realizing Vision 2020. It is totally different from manufacturing industry whereby the same construction team will not be able to produce the same products even though the projects have similar nature of construction. Owing to the complex, disputes between different parts within these interacting fragments is highly foreseeable. This study was conducted to identify the causes and effects of disputes in construction industry, as well as ways to mitigate disputes. Results from the survey conducted indicated that the causes of disputes in general between major parties involved in construction projects are various, with certain considered as major, others considered as quite significant and up to certain extent, some are considered of less significant but nonetheless could still give birth to disputes. Categorically the major effects of disputes are those that concerns time as well as money, while those consequences from the legal terms was also considered significant as the other potential effects of disputes. However, all parties involved do not seem to care much of the potential effects of disputes on their reputation as well on third parties. Dispute can effectively be avoided or mitigated by adopting certain or series of dispute avoidance activities. Although effective, these dispute avoidance approaches does not guarantee anybody full exclusion from experiencing disputes. Of all the dispute avoidance approach suggested the partnering approach was seen as the most effective but probably the hardest to be adopted. The content as well as the outcome of this study was hoped to be able to serve as a source of reference for various participants of construction industry with regards to the matters of disputes in construction industry.